- #1

steviet

- 3

- 0

## Homework Statement

The equations:

uz - 2e^(vz) = 0

u - x^2 - y^2 = 0

v^2 - xy*log(v) - 1 = 0

define z (implicitly) as a function of (u,v) and (u,v) as a function of (x,y),

thus z as a function f (x,y)

Describe the role of the inverse and implicit function theorems in the

above statement and compute

[tex]\partial[/tex]z/[tex]\partial[/tex]x(0,e).

(Note that when x=0 and y=e, u=e^2, v=1 and z=2)

## Homework Equations

Implicit and inverse function theorems

## The Attempt at a Solution

I'm finally starting to get a grasp on the 2 theorems and their

respective proofs (I hope), but as far as explaining their role in this

concrete example I'm a little lost.

If anyone can put me on the right path, it would be greatly appreciated.

(This is for an undergrad analysis course)

Last edited: